Branched GDGTs as Proxies in Surface Sediments From the South-Eastern Brazilian Continental Margin - Ceccopieri, Milena; Carreira, Renato S.; Wagener, Angela L. R.; Hefter, Jens; Mollenhauer, Gesine (Frontiers in Earth Science, 2019)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are membrane lipids produced by bacteria usually ascribed to soil and peat deposits. The presence of brGDGTs in marine sediments can thus be used to track terrigenous organic matter inputs to the continental margin and to infer the local continental mean annual air temperature (MAT) and soil pH. The proxy rationale is based on the degree methylation and cyclization of the brGDGTs from terrestrial bacteria, but recently evidence was found of river and oceanic production of brGDGTs with similar configuration, indicating the necessity to better constrain the applicability of the soil brGDGTs in the marine realm. Here we considered crenarchaeol and brGDGTs obtained in 46 core-top sediments from cross-margin transects in the Campos Basin in the Southwest Atlantic, with the goal to evaluate the effectiveness of the brGDGT-associated proxies in a region in the southeastern tropical Brazilian continental margin influenced by upwelling events and low terrigenous inputs. The separation of the 5- and 6-methyl brGDGTs proved to be essential for a better evaluation of the sources of brGDGTs in the environment. Direct evidence of input of terrigenous organic matter by the medium-sized Paraíba do Sul River and other small rivers in the region were observed. More importantly, the high proportions of ring-containing brGDGTs – and the consequent increased values of the #ringstetra – in the sediments deposited between 75 and 400 m water depths (mid-shelf to upper slope) were clear evidence of marine in situ production of brGDGTs. In some stations deeper than 1900 m, an increase in the acyclic 6-methyl hexamethylated compounds can also be ascribed to in situ production. Our results revealed that the initial soil signal is lost during transport and after river discharge in the Campos Basin, which compromise the use of brGDGTs to reconstruct the soil pH and MAT of the nearby land area.